Removal of Zn2+ and Pb2+ ions from aqueous solution using sulphonated waste polystyrene. Issue 4 (December 2015) - Ruziwa, Deborah; Chaukura, Nhamo; Gwenzi, Willis; Pumure, Innocent
Abstract: We report the use of sulphonated waste polystyrene (SWPS) in the removal of heavy metal ions from water. Waste polystyrene (WPS) comprising of high impact polystyrene (HIPS) and expanded polystyrene (EPS) collected from dump sites in Harare were activated through sulphonation to produce a cation-exchange resin. The presence of the sulphonic group was studied with fourier transform infrared spectroscopy (FTIR). Flame atomic absorption spectrometry (FAAS) was used to determine the concentrations of residual metals (Zn 2+, Pb 2+ ) after batch adsorption experiments. Sulphonated HIPS reduced Zn 2+ from 80 to 38.3 mg/L compared to 10–1.6 mg/L for sulphonated EPS. Similarly, sulphonated HIPS reduced Pb 2+ from 100 to 33 mg/L compared to 80–50.3 mg/L for sulphonated EPS. The adsorption data followed both the Langmuir and Freundlich isotherms and pseudo-second order kinetics. Maximum adsorption capacities as quantified by the Langmuir parameter q max for HIPS was 5.01 mg/g, EPS 0.38 mg/g for Zn 2+ and HIPS 6.80 mg/g, EPS 0.68 mg/g for Pb 2+ . The data were analysed using pseudo first order and pseudo second order Lagergren equation and the adsorption kinetics of the metals Pb 2+ and Zn 2+ was found to follow the pseudo second order kinetic model. Interpretation of the sorption data in terms of separation factor ( S F ) suggested that the removal of Pb 2+ and Zn 2+ from water mainly occurred through chemisorption.